PENGARUH KOMPETENSI STAF KEUANGAN TERHADAP KUALITAS LAPORAN KEUANGAN DESA (Studi Empris Seluruh Desa Di Kota Ambon) - Atarwaman, Rita J.D; Tuasamu, Dhevita (Jurnal Akuntansi, 2021)
This study aims to obtain empirical evidence about the Effect of Financial Staff Competence on the Quality of Village Financial Statements in Ambon City. The independent variable used is the competence of financial staff and the dependent variable is the quality of village financial reports. The population in this study were all employees who worked at the village office in the city of Ambon. The data used are primary data and the samples were collected using a saturated sampling method. The total financial staff totaling 46 employees in 30 village offices in Ambon city. The method of analysis of this research is using simple linear regression analysis. The results of this study indicate that the competence of financial staff has a significant effect on the quality of village financial reports in Ambon city.